The reduction of faecal calprotectin during exclusive enteral nutrition is lost rapidly after food re‐introduction. Issue 6 (25th July 2019) - Logan, Michael; Clark, Clare M.; Ijaz, Umer Zeeshan; Gervais, Lisa; Duncan, Hazel; Garrick, Vikki; Curtis, Lee; Buchanan, Elaine; Cardigan, Tracey; Armstrong, Lawrence; Delahunty, Caroline; Flynn, Diana M.; et al.
Summary: Background: Faecal calprotectin decreases during exclusive enteral nutrition in children with active Crohn's disease. It is unknown how faecal calprotectin changes during food re‐introduction and the influence of maintenance enteral nutrition. Aims: To study changes to faecal calprotectin during exclusive enteral nutrition and at food reintroduction, and explore associations with maintenance enteral nutrition. Methods: Children with Crohn's disease were followed during exclusive enteral nutrition and during food‐reintroduction. Faecal calprotectin was measured before, at 33 and 54 days of exclusive enteral nutrition, and at 17, 52 and 72 days after food‐reintroduction. Maintenance enteral nutrition use was recorded with estimated weight food diaries. Data are presented with medians and Q1:Q3. Results: Sixty‐six patients started exclusive enteral nutrition and 41 (62%) achieved clinical remission (weighted paediatric Crohn's disease activity index <12.5). Baseline faecal calprotectin (mg/kg) decreased after 4 and 8 weeks of exclusive enteral nutrition (Start: 1433 [Q1: 946, Q3: 1820] vs 33 days: 844 [314, 1438] vs 54 days: 453 [165, 1100]; P < .001). Within 17 days of food reintroduction, faecal calprotectin increased to 953 [Q1: 519, Q3: 1611] and by 52 days to 1094 [660, 1625] (both P < .02). Fifteen of 41 (37%) children in remission used maintenance enteral nutrition (333 kcal or 18% of energy intake). At 17 days of food reintroduction, faecal calprotectin was lower in maintenance enteral nutrition users than non‐users (651 [Q1: 271, Q3: 1781] vs 1238 [749, 2102], P = .049) and correlated inversely with maintenance enteral nutrition volume (rho: −0.573, P = .041), kcals (rho: −0.584, P = .036) and % energy intake (rho: −0.649, P = .016). Maintenance enteral nutrition use was not associated with longer periods of remission ( P = .7). Faecal calprotectin at the end of exclusive enteral nutrition did not predict length of remission. Conclusions: The effect of exclusive enteral nutrition on faecal calprotectin is diminished early during food reintroduction. Maintenance enteral nutrition at 18% of energy intake is associated with a lower faecal calprotectin at the early phase of food reintroduction but is ineffective in maintaining longer term remission.